Influência Da Teoria Do Comportamento Planejado Na Folga Orçamentária Mediado Pela Ética-Organizacional: Um Estudo De Caso Em Uma Construtora Na Região Oeste Do Paraná - Uliano, Tcharleni da Rocha Oviedo (2024)
Guided by the Theory of Planned Behavior (TPB), originating from the Theory of Reasoned Action (Ajzen, 1985), this research seeks to understand the influence of TPB on Budgetary Slack, mediated by organizational ethics. Recent studies highlight the relevance of organizational ethics and the need to align employee behaviors with the organization’s principles to ensure excellence in product and service delivery. Budgetary slack, which represents the difference between the budgeted cost and the actual cost, is a relevant financial indicator that can impact a company's financial health and project viability. However, the existing literature does not sufficiently address how organizational ethics can mediate the influence of TPB on budgetary slack. Although TPB is widely used to predict behaviors in various areas, its specific application to budget management, considering organizational ethics as a mediating variable, is still an underexplored area. This study aims to fill this gap, offering a deeper understanding of the factors shaping budgetary slack in organizations. The main objective is to investigate the influence of the Theory of Planned Behavior on budgetary slack, mediated by organizational ethics. The research aims to answer the question: "What is the influence of TPB on budgetary slack mediated by organizational ethics?". Adopting a quantitative and descriptive approach, the study used TPB as the theoretical framework. The sampling was carried out by convenience, focusing on civil engineers from a construction company, considering registered engineers. Data collection was conducted through a structured questionnaire on Google Forms. Data analysis was conducted with SmartPLS software and Structural Equation Modeling (SEM) to investigate the interactions between variables and evaluate the ethics in engineers' behavior. The results confirmed that TPB exerts a significant influence on budgetary slack, but this relationship is mediated by organizational ethics. The analysis revealed that individuals' Behavioral Intention (I) is a determining factor in budget management, with an average of 5.74 on a scale of 1 to 7. However, the direct relationship between TPB and budgetary slack was rejected, suggesting that TPB influences budgetary slack mainly through individuals' ethical behavior. Organizational ethics emerged as a crucial mediator, with higher levels of ethical behavior associated with lower budgetary slack. TPB also showed significant influence on the adoption of ethical practices, with attitudes, subjective norms, and perceived behavioral control being important factors. This study contributes to the literature by validating the application of TPB in budget management and highlighting organizational ethics as a key mediator. For business practice, it is suggested that strengthening organizational ethics can result in more transparent and effective budget management. Future research could explore other mediators and moderators of this relationship and expand the analysis to different sectors and cultural contexts, broadening the understanding of the factors influencing budgetary slack in various business environments.